Unroofing and argon mucosal remnant ablation of neonatal duodenal duplication cyst - Diego Falchetti; Antonio Dessanti; Marcella Falchetti; Gianpaolo Strusi (SpringerOpen, 2021)
Abstract Background Duodenal duplication cyst is an uncommon foregut malformation usually diagnosed at birth or during infancy. Differently from elsewhere, sited small bowel duplications cannot be removed with simple bowel resection, because of the proximity of the biliary and pancreatic ducts also possibly with abnormal course. Case presentation We report a duodenal duplication cyst in a newborn female requiring early surgery because of nutritional difficulties. The cyst was located adjoined to the second portion of the duodenum sharing part of its muscle wall with the bowel. It was treated by removal of all the esophytic cyst while the remaining mucosa on the common wall with the duodenum was ablated with argon plasma coagulation, preserving the bowel integrity. Early postoperative period was uneventful, and the child could be fed per os on the second day. Yearly follow-up was maintained until 16 years for the risk of recurrence and cancer change due to the incomplete excision. Clinic and echographic controls had always been stayed free from any sequelae. Conclusions Foregut duplications should be removed totally to prevent complications and the long-term risk of cancer, but a duodenal resection can be a harmful surgery in neonatal age. Duplication cysts that are impossible to remove totally can be treated by unroofing and argon plasma coagulation of mucosal surface remnants, avoiding the risks of major procedures also in newborns.